Reconciling Work and Family Responsibilities: A Global Perspective - Bardoel, E.A.; Cieri, H. De (ANIMA Indonesian Psychological Journal, 2007)
The issue of reconciling work and family responsibilities is a major concern for working men and women whether they live in industrialized and developed nations or developing nations. In- creasingly working adults in developing countries are struggling to reconcile work and family respon- sibilities. Although they will vary depending on the cultural context, effective family friendly policies require managers to be cognizant of a number of local factors that influence employees’ work and personal lives. These factors include culture and traditions, the role of key stakeholders, public poli- cies, community resources and infrastructure, and workplace practices and demographics. Isu memadukan pekerjaan dan tugas keluarga merupakan masalah utama bagi pria dan pe- rempuan yang bekerja baik mereka hidup di negara industri dan maju atau di negara berkembang. Makin banyak pekerja dewasa di negara berkembang berusaha dengan keras memadukan pekerjaan- nya dengan kewajiban keluarga. Sekalipun hal tersebut bervariasi tergantung konteks budayanya, ke- bijakan ramah keluarga yang efektif menuntut para manajer untuk bertanggung jawab terhadap se- jumlah faktor lokal yang memengaruhi kerja para pekerja dan kehidupan pribadinya. Faktor-faktor ini meliputi budaya dan tradisi, peran kunci mereka yang terkait, kebijakan umum, sumber daya dan in- frastruktur masyarakat, dan praktik-praktik di tempat kerja dan demografi.